A Note on the Association Between Thecaphora frezzii Infection and Peanut Pod Density - Bennett, R.S.; Rodriguez, Ana Valeria; Baldessari, Jorge Javier; Chamberlin, K.D.; Payton, M.E.; Wang, N. (American Peanut Research and Education Society, 2024)
The time and labor required to hand-screen germplasm are significant obstacles to developing cultivars resistant to peanut smut, but researchers have investigated few alternatives to manual disease evaluations. Although alternative approaches are available for separating materials based upon differences in density, it is unknown how healthy and infected pods differ in density, especially with the varying maturity levels present in real-world samples. For this reason, the pod densities from 13 peanut genotypes were estimated using a sand displacement approach. In addition, disease incidence and severity data were collected from a total of 45 plants representing 15 genotypes varying in resistance to peanut smut. As expected, the results from the pod density analyses showed significant differences between healthy mature and healthy immature pods. However, healthy mature and healthy immature pods were significantly more and less dense, respectively, than both mature infected and immature infected pods. While additional study is needed, it appears that methods employing differences in pod density may be useful for screening germplasm. Analyses of the disease incidence and severity data showed a strong positive correlation between the two disease measures, verifying a previous report. As a result, collecting disease incidence data alone may be sufficient for screening germplasm. These results may assist in developing more efficient phenotyping methods for screening germplasm for peanut smut resistance.